4.4x-27=2.9x+6

Simple and best practice solution for 4.4x-27=2.9x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4.4x-27=2.9x+6 equation:


Simplifying
4.4x + -27 = 2.9x + 6

Reorder the terms:
-27 + 4.4x = 2.9x + 6

Reorder the terms:
-27 + 4.4x = 6 + 2.9x

Solving
-27 + 4.4x = 6 + 2.9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2.9x' to each side of the equation.
-27 + 4.4x + -2.9x = 6 + 2.9x + -2.9x

Combine like terms: 4.4x + -2.9x = 1.5x
-27 + 1.5x = 6 + 2.9x + -2.9x

Combine like terms: 2.9x + -2.9x = 0.0
-27 + 1.5x = 6 + 0.0
-27 + 1.5x = 6

Add '27' to each side of the equation.
-27 + 27 + 1.5x = 6 + 27

Combine like terms: -27 + 27 = 0
0 + 1.5x = 6 + 27
1.5x = 6 + 27

Combine like terms: 6 + 27 = 33
1.5x = 33

Divide each side by '1.5'.
x = 22

Simplifying
x = 22

See similar equations:

| 67-20=2y-4 | | 4x(2+2)+4*6= | | 6y^2+28y-98=0 | | 3p-7=2(4-p) | | 5.6=10x+6.1 | | fx=3(2x-1) | | X/8+4=6 | | 1/4(8x-20)=1/3(15x-6) | | (3-7j)+(9-j)= | | Y-6.8=8 | | 2.5x+9-4.5x=1 | | 6-(6-10*343)= | | 9i/(8-5i) | | 5x-37.6=x | | x^2+16*x+1.2=0 | | 4(y+5)=32 | | 6m=2(5m+10) | | 0.5x+0.6=-1.9 | | [2(4-7)]= | | 3(2g+7)-6g-21=0 | | (x^4-y^4)*(x^4+y^4)=0 | | 2(x-8.8)=4.6 | | -12=4-21 | | 14x+93=261 | | 8=3x+4(-2x) | | 13-2(3x-6)=2(2-4x) | | 7x+5.03=4x+11 | | (x+3)*(x-4)=0 | | 43-1296-125= | | 9.9a+9.63=-88.38 | | y=1.2-3+3 | | y=1.3-3+3 |

Equations solver categories